Simulating the Dynamics and Influences of the West African Westerly Jet - Makinde, Akintunde Israel (Department of Environmental and Geographical Science, 2023)
The West African westerly jet (WAWJ) is a key rainfall producing system over West Africa. While past studies have examined the dynamics of the WAWJ and its influences on Sahelian rainfall, there is no information on how well the jet is simulated by contemporary climate models. This thesis examines the capability of the Coupled Model Intercomparison Project version 6 models (CMIP6) and the Atmospheric component of Model Prediction Across Scale (MPAS) in simulating the WAWJ, its moisture transport over West Africa, and its influence on Sahelian precipitation. Three types of climate dataset (observation, reanalysis, and simulations) were analysed in the thesis. The observation dataset (from the Climate Research Unit or ‘CRU') and the reanalysis dataset (from the European Centre for Medium-Range Weather Forecast Atmospheric Reanalysis, or ‘ERA5') were used to evaluate 26 CMIP6 models (for 35 years: 1980–2014) and MPAS (for 30 years: 1985–2014). To investigate the sensitivity of the simulated WAWJ to model resolution, two additional simulations were performed with MPAS, focusing on WAWJ strong years (1989, 1994, and 1999) and weak years (1986, 1990, and 2000). This thesis defined the WAWJ as a low-level westerly jet (with average maximum speed of 5 m s-1 ) at 925 hPa over the eastern Atlantic Ocean and over the West African coast and used standard statistical metrics to quantify the capability of the models in simulating the characteristics and influences of the WAWJ. The majority of the CMIP6 models capture the temporal and spatial structures of the WAWJ and agree with ERA5 that the jet attains its maximum speed in August. However, most simulated jets form earlier and are stronger than the observed jet. While most of the CMIP6 models capture the link between the jet and temperature distribution over West Africa, they struggle to reproduce the relationship between the jet and precipitation distribution over the sub-continent, especially over the Sahel. Most models failed to replicate the increase in the moisture transport (i.e., the eastward and north-eastward transports) associated with a stronger WAWJ, as in ERA5. Some models capture the increased moisture transport but do not translate it to increased precipitation over the Sahel. MPAS performs well in simulating various features in temperature, precipitation, and wind fields over West Africa, but with wet and warm biases over the region. It also simulates the WAWJ but the simulated jet forms too early and is too strong. In addition, the position and dynamics of the simulated jet differ from the observed jet because the model fails to capture the local pressure gradient force that induces the WAWJ over the Atlantic Ocean. The model underestimates the relationship between the WAWJ and Sahelian precipitation because it limits WAWJ moisture transports to the southern part of Sahel, in contrast to the observation. The sensitivity simulations show that increasing the horizontal resolution of the model does not improve the MPAS simulation of the WAWJ or the WAWJ moisture transport to the Sahel. The results of the study have application in improving the climate models for seasonal predictions and future projections over West Africa, especially over the Sahel.